Fiqh Learning Methodology in Responding Social Issues in Madrasa - Firman Mansir; Abdul Karim (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThis research aims to find out how students in Fiqh learning should have the ability to direct or form themselves in the learning process, what will be studied and to what extent, when, and how they will learn. Thus, students do not just become passive recipients in the learning process itself. In this case, it also emphasizes the importance of emotions, open communication and the values that each student has. This type of research uses a qualitative research methodology with a focus on literature research methods (data collection/sources). The results of this research show that Fiqh subjects in madrasas and public schools that should be able to raise awareness of students in terms of religion after studying Fiqh are increasingly motivated to practice it, but in fact, the students have not been able to adjust the learning maximally in their daily lives. Abstrak enelitian ini bertujuan untuk mengetahui bagaimana siswa dalam pembelajaran Fiqih harus memiliki kemampuan mengarahkan atau membentuk diri sendiri dalam proses pembelajaran, apa yang akan dipelajari dan sejauh mana, kapan, dan bagaimana mereka akan belajar. Dengan demikian, siswa tidak hanya menjadi penerima yang pasif dalam proses pembelajaran itu sendiri. Dalam hal ini juga ditekankan pada pentingnya emosi, komunikasi yang terbuka dan nilai-nilai yang dimiliki setiap siswa. Jenis penelitian ini menggunakan metodologi penelitian kualitatif dengan menitikberatkan pada metode penelitian kepustakaan (pengumpulan / sumber data). Hasil penelitian ini menunjukkan bahwa mata pelajaran Fiqih di madrasah dan sekolah negeri yang semestinya dapat meningkatkan kesadaran siswa dalam hal agama setelah mempelajari Fiqh semakin termotivasi untuk mengamalkannya, namun nyatanya siswa belum mampu menyesuaikan belajar secara maksimal dalam kehidupan sehari-hari mereka. How to Cite: Mansir, F., Karim, A. (2020). Fiqh Learning Methodology in Responding Social Issues in Madrasa. TARBIYA: Journal of Education in Muslim Society, 7(2), 241-251. doi:10.15408/tjems.v7i2.20024.